EMOSI POSITIF DALAM RESOLUSI KONFLIK: POSITIVE EMOTION AT CONFLICT RESOLUTION - Ridwan Ridwan (Jurnal Psikologi Jambi, 2018)
ABSTRACT Introduction The conflict at Kabupaten Kerinci is an complex issues, it causes a lot disadvantage, either death, losing homes or properties.Various viewpoints trying to understand how conflict and conflict resolution in Kerinci. In this study, the researchers try to focus how the emotions of the villagers of the various Villages that existed in the Kerinci Regency of conflicts in a large scale happened for a decade. Method This research uses the phenomenology psychology approach, with qualitative method through interviews and observation on the villagers and leader from six villages. Result The result of this research shows that the positive emotions which arise when conflict resolution are empathy, sense of familiy, the feeling of prosperous and conducive, and subjective well being Conclusion and Recommendation From those results, the researchers concluded that the villagers’ positive emotions are conditional meaning that negotiations, de-escalation of the conflict, social interaction, win-win solution, cultural event. Keywords : Positive emotion, Conflict resolution, Kerinci